2005
DOI: 10.1055/s-2005-870132
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal Ultrasound for the Evaluation of Patients with Biliary Strictures and No Abdominal Mass on Computed Tomography

Abstract: IDUS is a valuable adjunct to ERCP in the characterization of biliary strictures in patients who present with painless jaundice in the absence of a culprit mass on abdominal imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 13 publications
2
52
0
1
Order By: Relevance
“…More recently, techniques such as intraductal ultrasound (IDUS) and cholangioscopy have been used to obtain direct biopsy specimens. IDUS with biopsy increased the accuracy of ERCP from 58%-60% to 83%-90% in distinguishing benign and malignant strictures [33] . These diagnostic modalities appear very promising in differentiating benign and malignant biliary lesions, although they are highly expert-dependent and are still not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, techniques such as intraductal ultrasound (IDUS) and cholangioscopy have been used to obtain direct biopsy specimens. IDUS with biopsy increased the accuracy of ERCP from 58%-60% to 83%-90% in distinguishing benign and malignant strictures [33] . These diagnostic modalities appear very promising in differentiating benign and malignant biliary lesions, although they are highly expert-dependent and are still not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of 62 patients with biliary strictures, IDUS had a diagnostic sensitivity of 90% and specificity of 93% [143] . In another study by Stavropoulos et al [144] , IDUS increased the diagnostic accuracy of ERCP from 58% to 90% in a series of patients with biliary strictures and no mass detected on CT.…”
Section: Intraductal Ultrasound (Idus)mentioning
confidence: 99%
“…Intraductal ultrasonography can provide the local staging to select patients with cholangiocarcinoma who benefit from surgical resection [43][44][45][46] . Recently, Stavropoulos et al [47] reported that intraductal ultrasonography increased the www.wjgnet.com…”
Section: Intraductal Ultrasonographymentioning
confidence: 99%